2013
DOI: 10.3109/10903127.2013.792891
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Tranexamic Acid after 12-Week Storage at Temperatures from –20°C to 50°C

Abstract: Except for the finding that TXA ampoules cracked when frozen, this study indicated that the drug remains effective when stored under conditions likely to be encountered in the prehospital environment and outside the manufacturer's recommended temperature range for at least 12 weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 20 publications
0
16
0
Order By: Relevance
“…TXA is stable in a wide variety of field conditions for up to 12 weeks. 41 The prehospital phase includes the intervention arm in which subjects receive 1 g of TXA or the control arm in which subjects receive 1 g of identical placebo. Both TXA and the placebo will be diluted in 100 mL of normal saline (prepared on the helicopter) and infused intravenously over 10 minutes.…”
Section: Design Of the Staamp Trialmentioning
confidence: 99%
“…TXA is stable in a wide variety of field conditions for up to 12 weeks. 41 The prehospital phase includes the intervention arm in which subjects receive 1 g of TXA or the control arm in which subjects receive 1 g of identical placebo. Both TXA and the placebo will be diluted in 100 mL of normal saline (prepared on the helicopter) and infused intravenously over 10 minutes.…”
Section: Design Of the Staamp Trialmentioning
confidence: 99%
“…8,9 Tranexamic acid is heat-stable, inexpensive, and widely available and has a long shelf life. 10,11 The World Maternal Antifibrinolytic (WOMAN) trial, for which we were investigators, showed that the early administration of tranexamic acid led to a lower risk of death due to bleeding than placebo among women with postpartum hemorrhage and had an acceptable safety profile. 12 The treatment was similarly effective when bleeding was attributable to uterine atony.…”
Section: Finding Better Ways To Prevent Postpartum Hemorrhagementioning
confidence: 99%
“…The CRASH-2 study has shown a decrease in mortality with the administration of TXA if administered within the first 3 hours following the injury 37 38. Moreover, TXA is cheap, not altered by extreme temperatures39 and remains efficient even in the face of acidosis 40. Widely used in civilian health systems, TXA has proven its benefit on the battlefield with the MATTERs study41 and is nowadays part of the tactical combat casualty care 4 42…”
Section: Haemostatic Resuscitationmentioning
confidence: 99%